The THE INFLUENCING OF INTERNAL AND EXTERNAL FATORS ON SHARE RETURN (CASE STUDY ON BANKING GO PUBLIC IN INDONESIA) - Pariang Siagian; Luqman Hakim (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
The purpose of this research is to examine the various factors that can affect operational efficiency and it impacts on share return in banking companies listed on the Indonesia Stock Exchange during 2015 and 2020 years. Theoretical basis of a bank's efficiency can mitigate and control operating cost to operating income, include to share price/return that can be affected by internal factors such as capital adequacy ratio, loan-to-deposit ratio, and net interest margin; and external factors as though macroeconomic indicators like inflation rate and exchange rate. The research method used linear multiplier regression by conducting various tests, including descriptive statistics, determination, regression equation, hypothesis, and implication tests. This study finds that the Capital Adequacy Ratio (CAR), Loan-To-Deposit Ratio (LDR), Inflation rate and Exchange rate have a significant effect on share return, whereas Operating Cost to Operating Income and Net Interest Margin have not an influence on Share Return. The research’s usefulness is terribly important for several sides include managers, companies, and policymakers interested in addressing banking business operations and improving financial performance and mitigation strategies. The study highlighted that operating efficiency is not only related to internal factors but also external factors, hence it might be obtained of competitive advantage. Otherwise, this study has limitations, the parties including internal and external factors, as well as the research period, can be expanded for future researchers.